Teaching Performance of Students of the Faculty of Education, Sohag University: "An Evaluative Study in Light of Teacher Preparation Standards" - Saleh, Shoeb Gamal; AlAli, Rommel Mahmoud (Journal of Ecohumanism, 2024)
This study aimed to evaluate the teaching performance of student teachers at the Faculty of Education, Sohag University, based on teacher preparation standards. The research employed a descriptive-analytical approach and developed a checklist comprising 64 sub-skills categorized under seven main standards: lesson planning, classroom management and student interaction, use of teaching strategies, integration of educational tools and technologies, personal traits and interpersonal skills, mastery of subject matter, and student learning assessment. The performance of 50 student teachers from scientific and literary disciplines was assessed using an observation checklist. The results revealed that teaching performance was moderate across six standards and good in the "personal traits and interpersonal skills" standard. Statistically significant differences (p ≤ 0.01) were found in favor of scientific students compared to their literary counterparts. The study emphasized the need to enhance student teachers’ skills to improve the quality of teaching performance.